People's theatre and Shakespeare in wartime: Donald Wolfit's King Lear in London and Leeds, 1944–45. (2nd January 2016) - Raw, Laurence
Abstract : Through a case study of Donald Wolfit's "King Lear" as performed in various British venues in 1944 and 1945, this article will try to account for Wolfit's extraordinary popularity, as well as speculating on why his contribution to the British war effort has been largely forgotten. It will also suggest that the production was significant in its time, as it took place during a period of major social and political upheaval. The experiences of war brought people from different cultures together as never before. Bearing this in mind, Wolfit tried to create the kind of popular theatre that would inspire everyone to fight for a better collective future.